Proteoglycan populations of baboon ( Papio papio) cartilages from different anatomical sites : Gel electrophoretic analysis of dissociated proteoglycans and of fractions obtained by density gradient centrifugation - Stanescu, Victor; Maroteaux, Pierre; Sobczak, Eliane (Biochimica et biophysica acta, 1980)
Proteoglycans extracted by 4 M guanidinium chloride from different cartilages and vertebral discs of young baboons ( Papio papio) were purified by ion-exchange chromatography and assessed by gel electrophoresis. Proteoglycans fractionated by equilibrium density gradient centrifugation under ‘dissociative’ conditions were similarly purified and assessed. 1. (1) Non-fractionated proteoglycans from articular, nasal, laryngeal, tracheal, costal, vertebral plate and ear cartilage and from anulus fibrosus gave three metachromatic bands on gel electrophrresis: two broad, closely running bands (I and II) and a faster, more discrete band (III). The migrations rates of corresponding bands of various cartilages were similar, with minor differences in staining intensity. Gel electrophoresis of material fractionated on the gradient indicated the presence of bands with the same migration and appearance as those found for the unfractionated proteoglycans and also partial separation of bands (bouyant density T > II > III). 2. (2) Non-fractionated proteoglycans from growth cartillage yielded bands I and II only. Small amounts of material corresponding to band III were detected in the upper fractions of the gradients. 3. (3) Proteoglycans from nucleus pulposus migrated as two diffuse bands corresponding to bands I and II. The two bands were partially separated in the gradients and an additional very slow band was formed in the middle fractions of the gradients. 4. (4) Proteoglycans from knee menisci contained a densely stained band of corresponding mobility to band III. Faint bands corresponding to band I and II were also detected. The bands were partially separated in the gradients.